O Partido Socialismo e liberdade no Rio de Janeiro/RJ: um olhar investigativo sobre as dinâmicas do partido nas eleições municipais de 2016 e 2020 - Silva, Laila Borges da (2022)
This research aims to understand the Partido Socialismo e Liberdade (PSOL) in Rio de Janeiro/ RJ in its organization and growth strategies in the municipality. Founded in 2004, it is today one of the most influential left-wing parties in municipal politics, having, since 2016, surpassed the Partido dos Trabalhadores (PT) in seats in the House. The paper locates the PSOL as a left- wing party in Brazilian society and it discusses the PSOL in the municipality of Rio de Janeiro, focusing on its organizational dynamics and participation in electoral processes. At this point, the data from the Superior Electoral Court (TSE) of results by electoral zone, in the voting of councilors elected by the party, in the years 2016 and 2020, are brought. Finally, the dimension of the figure of Marielle Franco, councilwoman executed in the year 2018, and its impacts on the party, the PSOL, at the local level is worked. For the research, the methodology was divided into two axes: documentary analysis, dealing with both the TSE voting results and the party's regulations and pamphlets, and fieldwork, which included semi-structured interviews with leaders and monitoring of events. The COVID-19 pandemic had a large impact on this work, which had its execution halted and then, within the possible limits, moved to the virtual. As result of this research, we observe the centrality of the territorial nuclei in the project of growth and capillarization of the PSOL in Rio de Janeiro and the dimension of the figure of Marielle Franco today in the party, with the narrative of "Marielle's seeds".